2016
DOI: 10.1016/j.jaut.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Inherent ER stress in pancreatic islet β cells causes self-recognition by autoreactive T cells in type 1 diabetes

Abstract: Type 1 diabetes (T1D) is an autoimmune disease characterized by pancreatic β cell destruction induced by islet reactive T cells that have escaped central tolerance. Many physiological and environmental triggers associated with T1D result in β cell endoplasmic reticulum (ER) stress and dysfunction, increasing the potential for abnormal post-translational modification (PTM) of proteins. We hypothesized that β cell ER stress induced by environmental and physiological conditions generates abnormally-modified prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 101 publications
(146 reference statements)
3
88
0
Order By: Relevance
“…The activation of PAD enzymes requires high levels of cytosolic Ca 2+ (11), which is favored by ER dysfunction in combination with excessive insulin demand. A similar process has been described for the Ca 2+ -dependent PTM enzyme tissue transglutaminase 2 in which activity is increased by ER stress, leading to b-cell stress-dependent immunogenicity (10). In this scenario, our observation that GRP78 is translocated to the plasma membrane upon cytokine exposure in rodent b-cells (17) and human islets (S. Vig, L.O., unpublished observations) is noteworthy.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The activation of PAD enzymes requires high levels of cytosolic Ca 2+ (11), which is favored by ER dysfunction in combination with excessive insulin demand. A similar process has been described for the Ca 2+ -dependent PTM enzyme tissue transglutaminase 2 in which activity is increased by ER stress, leading to b-cell stress-dependent immunogenicity (10). In this scenario, our observation that GRP78 is translocated to the plasma membrane upon cytokine exposure in rodent b-cells (17) and human islets (S. Vig, L.O., unpublished observations) is noteworthy.…”
Section: Discussionsupporting
confidence: 71%
“…Many of the triggers associated with type 1 diabetes, such as inflammatory cytokines, free radicals, and viral infections, result in endoplasmic reticulum (ER) or oxidative stress (3)(4)(5)(6)(7)(8)(9)(10)(11). These stresses can lead to modifications of b-cell proteins, including posttranslational modifications (PTMs) (10,(12)(13)(14)(15)(16)(17), mRNA alternative splicing, hybrid peptide formation (18,19), and nonconventional translation, potentially generating neoepitopes against which no tolerance exists in the immune system (20). In several autoimmune diseases, such as rheumatoid arthritis, multiple sclerosis, systemic lupus erythematosus, and celiac disease, PTM proteins are established autoantigens (21,22), but their relevance in type 1 diabetes is only starting to be explored.…”
mentioning
confidence: 99%
“…Recombinant proteins for ASIT cost more to produce than DNA and may not undergo certain post-translational modifications during production. Many epitopes recognized by autoreactive T cells turn out to be modified or hybrid peptides,3, 4, 6, 7, 39 which further suggests that conventional ASIT strategies are suboptimal and limited. Thus, incorporation of hybrid peptides or mimotopes emulating post-translationally modified peptides identified in human patients will be required to more efficiently engage and tolerize diabetogenic T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory milieu also impacts post‐translational modification (PTM) processes: the calcium‐dependent enzymes tissue transglutaminase 2 and peptidyl amine deaminase were shown to be activated in islets and dendritic cells leading to increase in deamidation and citrullination of islet‐autoantigens, improving their potency to bind HLA molecules and their immunogenic properties . Such modifications have been demonstrated to increase visibility of β‐cells to the immune system as seen by the increased T‐cell response observed after chemical induction of ER stress in β‐cells . Recently, we demonstrated that translation of the insulin mRNA was also influenced by environmental modifications and that ER stress induction led to recruitment of ribosomes at alternative translation initiation sites and to translation of a highly immunogenic insulin‐gene derived polypeptide targeted by T‐cell autoreactivity in T1D patients .…”
Section: Introductionmentioning
confidence: 98%
“…[6][7][8][9][10] Such modifications have been demonstrated to increase visibility of β-cells to the immune system as seen by the increased T-cell response observed after chemical induction of ER stress in β-cells. 11 Recently, we demonstrated that translation of the insulin mRNA was also influenced by environmental modifications and that ER stress induction led to recruitment of ribosomes at alternative translation initiation sites and to translation of a highly immunogenic insulin-gene derived polypeptide targeted by T-cell autoreactivity in T1D patients. 12 Indeed, the rate of β-cell destruction increased upon inflammatory stress, while expression of Arnaud Zaldumbide and Bart O. Roep contributed equally to this work defective ribosomal products (DRIPs) of insulin was increased by the calcium-dependent stressor thapsigargin, but not by calciumindependendent tunicamycin.…”
Section: Introductionmentioning
confidence: 99%